2013
DOI: 10.1002/bies.201300138
|View full text |Cite
|
Sign up to set email alerts
|

Closing the (nuclear) envelope on the genome: How nuclear lamins interact with promoters and modulate gene expression

Abstract: The nuclear envelope shapes the functional organization of the nucleus. Increasing evidence indicates that one of its main components, the nuclear lamina, dynamically interacts with the genome, including the promoter region of specific genes. This seems to occur in a manner that accords developmental significance to these interactions. This essay addresses key issues raised by recent data on the association of nuclear lamins with the genome. We discuss how lamins interact with large chromatin domains and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 98 publications
(191 reference statements)
1
41
0
Order By: Relevance
“…1 Interactions of nuclear lamins with chromatin occur through large genomic areas of »0.1-10 megabases (mb). These domains have been termed lamina-associated domains (LADs) with the implication that lamins associate with chromatin only at the nuclear lamina, that is, at the nuclear periphery [2][3][4][5] (reviewed in [6][7][8] ). LADs have initially been discovered by DamID (DNA adenine methyltransferase [Dam] identification, a proximity assay).…”
Section: Introductionmentioning
confidence: 99%
“…1 Interactions of nuclear lamins with chromatin occur through large genomic areas of »0.1-10 megabases (mb). These domains have been termed lamina-associated domains (LADs) with the implication that lamins associate with chromatin only at the nuclear lamina, that is, at the nuclear periphery [2][3][4][5] (reviewed in [6][7][8] ). LADs have initially been discovered by DamID (DNA adenine methyltransferase [Dam] identification, a proximity assay).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic gene silencing can be divided into three processes: initiation of gene silencing, maintenance of the repressive chromatin state, and inheritance through S-phase and mitosis 4 , 9 , 10 . In addition to these processes, recent studies have demonstrated the functional importance of spatial chromatin organization in epigenetic control 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, lamins have been shown to play important roles in many essential cellular functions, including gene expression, DNA replication, DNA repair, chromatin organization, cell proliferation and differentiation, cell signaling, and cell division (Dechat et al 2008;Zuela et al 2012;Burke and Stewart 2013;Choi and Worman 2014;Collas et al 2014;Kennedy and Pennypacker 2014;Shimi and Goldman 2014). Despite all of their important functions, recent studies showed that lamins are not required for the proliferation and differentiation of ESCs and the proliferation of mouse embryonic fibroblasts and keratinocytes but seem to be important for later developmental processes, including tissue formation and homeostasis and organogenesis (Kim et al 2011Jung et al 2014).…”
mentioning
confidence: 99%